Influence and Persuasion (HBR Emotional Intelligence Series). - Review, Harvard Business. (HBR emotional intelligence series., 2017)
Changing hearts is an important part of changing minds. With research into how appeals to human emotion can help you make your case and earn authority as a leader, this book presents both comprehensive frameworks for developing a influence and small, simple tactics that you can use to convince others every day.--